Pemberdayaan Masyarakat Pemula UMKM Mie Basah Kelurahan Paccerakkang Kota Makassar Melalui Digitalisasi - Bachtiar, Irmah Halimah; Gafur, Gafur; Supiati, Supiati; Bachtiar, Ayu Darmawan; Hasan, Azizah (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
The magnitude of the role of MSMEs as the backbone of the national economy is evidenced from data from the Ministry of Cooperatives and Small and Medium Enterprises for 2022 that the number of MSMEs in South Sulawesi has experienced a significant increase and in 2022 it will reach 268,299 units. However, this condition contrasts with Mr. Rahman Robin's MSMEs Mie Basah Manga Tiga, which does not provide optimal results, and sales sometimes experience a decline. The purpose of this service is to develop the Mangga Tiga wet noodle business through digital utilization. One of the government's newest programs in supporting MSME growth is "Ministry of Finance One Supports MSMEs Growing through Digitalization and Globalization Towards Advanced Indonesia". Based on this program, we consider it important to increase the wet noodle business through digitization. The method used is the provision of materials as well as training and assistance regarding the preparation of financial reports, digital marketing and packaging innovation. The results of the activity show that partners are able to compile simple financial reports, partners are able to carry out digital marketing through several online applications, and the new packaging of mangga tiga wet noodles is equipped with a product label which already contains a business license and halal certificate.Keywords: MSMEs; Wet noodle; DigitizationAbstrak: Besarnya peranan UMKM  sebagai tulang punggung perekonomian nasional dibuktikan dari data Kemenkop UKM tahun 2022 bahwa jumlah UMKM di Sulawesi Selatan mengalamai peningkatan yang signifikan dan di tahun 2022 mencapai 268.299 unit. Namun kondisi demikian kontras dengan pelaku UMKM Mie Basah Manga Tiga milik Bapak Rahman Robin yang tidak memberikan hasil yang optimal bahkan penjualan terkadang mengalami penurunan. Tujuan dilaksanakan pengabdian ini adalah untuk mengembangkan usaha mie basah Mangga Tiga melalui pemanfaatan digital. Salah satu program terbaru pemerintah dalam mendukung pertumbuhan UMKM adalah â€œKemenkeu Satu Mendukung UMKM Tumbuh melalui Digitalisasi dan Globalisasi Menuju Indonesia Majuâ€. Berdasar dari program tersebut kami menganggap penting meningkatkan usaha mie basah melalui digitalisasi.  Metode yang digunakan adalah pemberian materi serta pelatihan dan pendampingan mengenai penyusunan laporan keuangan, pemasaran digital dan inovasi packaging. Hasil kegiatan menunjukkan bahwa mitra sudah mampu menyusun laporan keuangan sederhana, mitra mampu melakukan pemasaran digital melalui beberapa aplikasi online, serta kemasan baru dari mie basah mangga tiga sudah dilengkapi label produk yang di dalamnya sudah terdapat izin usaha dan sertifikat halal.Kata kunci: UMKM; Mie Basah; Digitalisasi